Pesantren dan Pembaharuan - Ruswanto, Ruswanto (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Boarding  School  is  the  oldest  Islamic  institution  in  Indonesia  which  has  a  very important role in the spread and consolidation of public adherence to Islam. But since when actually boarding school began to stand, is not known for certain, but researchers have found that  in  the  16th  century  boarding  school  institutions  has  grown.  Among  the  researchers  are also  differences  of  opinion  about  the  origins  of  the  term  and  the  Pondok  Pesantren,  some argue  comes  from  within  and  in  part  argues  from  the  outside.  The  cottage-boarding  school originally  taught  about  fiqh,  tafsir,  tasawwuf  and  the  classics  as  a  feature  of  Pesantren traditional,  then  with  the  rise  of  reformism  as  the  influence  of  scientific  and  technological advances, the boarding school was also affected reformism, and this is a positive development the boarding school itself. But although affected reformism boarding school, boarding school never  taught  radicalism  /  extremism,  because  schools  are  actually  contrary  to  Islamic teachings and ways of proselytizing Islam.